Hubungan Tingkat Pengetahuan dan Sikap terhadap Kejadian Penyakit Diabetes Mellitus di Gampong Lampanah Ranjo Kabupaten Aceh Besar Tahun 2025 - Phossy Vionica Ramadhana; Irma Hamisah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Diabetes mellitus (DM) is a non-communicable disease whose prevalence continues to increase and has become a major public health problem worldwide, including in Indonesia. Adequate knowledge and positive attitudes toward DM are expected to promote preventive behaviors and reduce the risk of developing the disease. This study aimed to analyze the relationship between knowledge and attitudes and the incidence of diabetes mellitus in Gampong Lampanah Rajo. This study employed a quantitative design with a cross-sectional approach. A total of 41 respondents were selected using an accidental sampling technique. Data were collected using a structured questionnaire and analyzed through univariate and bivariate analyses using the Chi-square test with a significance level of 0.05. The results showed that most respondents did not have diabetes mellitus (90.2%), had good knowledge (80.5%), and demonstrated positive attitudes (85.4%). Among respondents with good knowledge, 90.9% did not have diabetes mellitus, compared to 87.5% among those with poor knowledge. Respondents with positive attitudes who did not have diabetes mellitus accounted for 88.6%, while all respondents with poor attitudes (100%) did not have diabetes mellitus. Statistical analysis revealed no significant relationship between knowledge (p=1.000) or attitudes (p=1.000) and the incidence of diabetes mellitus. It can be concluded that knowledge and attitudes were not associated with the incidence of diabetes mellitus among the study respondents.